A Novel del(20q) in Aggressive Nodal Marginal Zone Lymphoma. (12th February 2013) - Kern, Jason B.; Duff, Deiter J.; Odem, Jamie L.; Esebua, Magda; Smith, Lisa R.; Doll, Donald; Wang, Michael
Abstract : This is a case report of a previously undescribed 20q chromosomal deletion (del(20q)) in marginal zone lymphoma (MZL). A 54-year-old Caucasian male presented with an enlarging neck mass and multiple violaceous skin nodules over his chest. Biopsy of the neck mass and cervical lymph nodes revealed MZL. Cytogenetic evaluation of both lymph node and bone marrow tissue revealed del(20q). This was an unexpected finding, as del(20q) is associated with myelodysplastic syndromes and myeloproliferative neoplasms and rarely seen in diffuse large B-cell lymphoma, follicular lymphoma, and T-cell lymphoma, but has not previously been described in MZL. We describe the case presentation and histologic findings and discuss the significance of this novel finding.